A multicenter study to evaluate ceftaroline breakpoints: Performance in an area with high prevalence of methicillin- resistant Staphylococcus aureus sequence type 5 lineage (2019)
ABSTRACT Ceftaroline (CPT) is a broad-spectrum agent with potent activity against methicillin-resistant Staphylococcus aureus (MRSA). The sequence type 5 (ST5) Chilean-Cordobés clone, associated with CPT nonsusceptibility, is dominant in Chile, a region with high rates of MRSA infections. Here, we assessed the in vitro activity of CPT against a collection of MRSA isolates collected between 1999 and 2018 from nine hospitals (n 320) and community settings (n 41) in Santiago, Chile, and evaluated performance across testing methodologies. We found that our hospitalassociated isolates exhibited higher CPT MIC distributions (MIC50 and MIC90 of 2 mg/liter) than the community isolates (MIC50 and MIC90 of 0.5 mg/liter), a finding that was consistent across time and independent of the culture source. High proportions (64%) of isolates were CPT nonsusceptible despite the absence of CPT use in Chile. Across methodologies, the Etest underestimated the MIC relative to the gold standard broth microdilution (BMD) test (MIC50 and MIC90 of 1 and 1.5 mg/liter, respectively). There was low (51%) categorical agreement (CA) between Etest and BMD results across CLSI and EUCAST breakpoints. The recent revision of CLSI guidelines abolished “very major error” (VME) from the previous guidelines (81%), which perform similarly to the EUCAST guidelines. The level of concordance between CLSI and EUCAST for BMD testing and Etest was 95%. Disk diffusion performed poorly relative to BMD under CLSI (CA, 55%) and EUCAST (CA, 36%) guidelines. Comparison of EUCAST to CLSI for disk diffusion (with EUCAST used as the reference) showed low agreement (CA, 25%; VME, 70%). In summary, CPT-nonsusceptible MRSA are dominant in clinical settings in Chile. Our results provide data to support the reevaluation of CPT breakpoints and to improve agreement across methodologies and agencies.